Seattle to Brussels Network : investment and competition negotiations in the WTO - what's wrong with it and wath are the alternatives? - Walker-Leigh, Vanya; Wandel, Alexandra (Brussels: Seattle to Brusssels Network; Berlin, 2002)
"Vanya Walker-Leigh; Alexandra Wandel... et al."